Oral Corrective Feedback: Exploring The Relationship Between Teacher’s Strategy and Student's Willingness to Communicate - Lailatus Sa'adah (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
Corrective feedback has become a big issue in second language acquisition. Its effectiveness when implemented in the class is still the subject of debate. Moreover, its impact on second language learners’ performance is also a topic of discussion. Recently, there has been a growing interest in the role of corrective feedback as a research topic in EFL context. Most researches showed that corrective feedback has a positive effect on EFL learners. Although there has been a growing research concern on the effectiveness of oral corrective feedback, its impact and its application in EFL classroom setting, limited studies examined the relationship between teachers’ corrective feedback and students’ willingness to communicate. Therefore, this case study explores how oral corrective feedback is implemented in the class and its effect on the students’ willingness to communicate. For this purpose, interviews and observations were used to collect data from a teacher and tenth grade students of senior high school in the academic year 2016/2017. The findings showed that there are three types of oral corrective feedback found in the class: explicit correction feedback, metalinguistic feedback, and clarification request feedback. Moreover, the students frequently make phonological errors and semantic errors while speaking. In regard to the students’ uptake, acknowledgement, repetition, off-target, and peer-repair are mostly found from the teacher and students interaction. The students also insist that the teacher’s oral corrective feedback does not disturb teacher and students classroom interaction.